Bi-directional regulation of cognitive control by distinct prefrontal cortical output neurons to thalamus and striatum - Sybren F. de Kloet (Nature Portfolio, 2021)
This study presents an anatomical, neurophysiological and functional characterization of four distinct prefrontal populations that project to striatal and thalamic sub-regions. The authors show that each of these populations have a discrete role in the regulation of cognitive control.